Konsep Punishment dan Reward dalam Pembelajaran Berdasarkan Al-Qur'an dan Hadis - Yuniartin, Titin; Khuluq, Mas Faiqul; Siswanto, Wawan; Firmansyah, Ade Aang (Trends in Applied Sciences, Social Science, and Education, 2024)
The concepts of punishment and reward are essential strategies in the learning process to motivate and discipline learners. From an Islamic perspective, the Qur'an and Hadith provide strong foundations for these concepts. This study aims to explore the values of punishment and reward in the Qur'an and Hadith and their implementation in education. Using a qualitative approach and literature review method, this study analyzes relevant verses and prophetic traditions. The findings show that the concept of reward is prioritized as a form of positive motivation, while punishment is used proportionally to correct behavior without causing trauma. This article recommends an Islamic value-based educational approach that balances reward and punishment to create effective learning.